Counseling on balanced nutrition 'isi piringku' to prevent stunting in toddlers aged 1-5 years - Imardiani Imardiani; Dodik Firnando; Triya Cindy Franciska; Riska Wulandari; Tiara Medira; Intan Pramono; Wanda Hamidah; Suci Romadhona; Indah Tri Lestari; Intan Nurmala (Community Empowerment, 2024)
Toddlers are a vulnerable group affected by child nutrition issues, one of which is stunting. Stunting is a condition where a child experiences growth impairment, resulting in their height not matching their age due to chronic nutritional problems, specifically prolonged nutrient deficiency. Stunting is caused by two factors: the history of exclusive breastfeeding and maternal knowledge about nutrition. This community service activity aims to increase public knowledge about balanced nutrition guidelines through the "isi piringku" campaign. The activity is carried out using educational methods, utilizing posters and leaflets as aids for 55 participants. The results of the activity show an increase in knowledge after the "isi piringku" campaign, where before the campaign, the level of good knowledge was only 9.09% and increased to 81.82%.